Analysis of Inter-Individual Bacterial Variation in Gut of Cicada Meimuna mongolica (Hemiptera: Cicadidae). Issue 1 (25th September 2015) - Zhou, Wenting; Nan, Xiaoning; Zheng, Zhou; Wei, Cong; He, Hong
Abstract : Intestinal bacterial community plays a crucial role in the nutrition, development, survival, and reproduction of insects. When compared with other insects with piercing-sucking mouthparts, the habitats of cicada nymphs and adults are totally different. However, little is known about the differences in the gut bacterial communities in the nymphs and adults within any cicada species. The diversity of bacteria in the gut of nymphs and adults of both genders of Meimuna mongolica (Distant) was studied using the denaturing gradient gel electrophoresis (DGGE) method. Few inter-individual variations among gut microbiota were observed, suggesting that M. mongolica typically harbors a limited and consistent suite of bacterial species. Bacteria in the genera Pseudomonas and Enterobacter were the predominant components of the gut microflora of M. mongolica at all life stages. Bacteria of Pantoea, Streptococcus, and Uruburuella were also widespread in the cicada samples but at relatively lower concentrations. The relative stability and similarity of the PCR-DGGE patterns indicate that all individuals of this cicada species harbor a characteristic bacterial community which is independent from developmental stages and genders. Related endosymbionts that could be harbored in bacteromes of cicadas were not detected in any gut samples, which could be related to the cicada species and the distribution of these endosymbionts in the cicada cavity, or due to some of the possible limitations of PCR-DGGE community profiling. It is worthwhile to further address if related cicada endosymbiont clades distribute in the alimentary canals and other internal organs through diagnostic PCR using group-specific primer sets.